Moisture effect on the diffusion of Cu ions in Cu/Ta2O5/Pt and Cu/SiO2/Pt resistance switches: a first-principles study - Bo Xiao; Satoshi Watanabe (Science and Technology of Advanced Materials, 2019)
Cu/Ta2O5/Pt and Cu/SiO2/Pt are two of the most promising resistance switches. From experimental observations, it is speculated that the presence of H2O in the amorphous Ta2O5 and SiO2 (a-Ta2O5 and a-SiO2) facilitates the rate-limiting step during the switching process. This rate-limiting step is essentially the diffusion of Cu ions along the nanopores of the amorphous. To better understand this behavior and obtain a detailed examination of the atomic structures, a first-principles simulation was conducted. In addition, we investigate the diffusion behaviors of Cu ions in bare a-Ta2O5 nanopore and in the one covered with H2O–together with those in a-SiO2 nanopore. Our work reveals that Ta and Si atoms on the sidewalls of bare a-Ta2O5 and a-SiO2 nanopores are in the unsaturated (TaO5) and saturated (SiO4) forms, respectively. Consequently, H2O molecules are adsorbed on the nanopore sidewall strongly in the case of a-Ta2O5, and weakly in a-SiO2, by forming O-Ta and H∙∙∙O bonds, respectively. This can explain the experimental observation that the desorption of H2O occurs only at high temperatures for a-Ta2O5 films, while it is observed for a-SiO2 even when the temperature is low. The calculated diffusion barrier of Cu ions in a-Ta2O5 nanopores covered with H2O is about 0.43 eV, which is much lower than that without H2O (~1.40 eV). In view of the similar chemical environments of O and the adsorbed Cu ions in a-SiO2 and a-Ta2O5 nanopores, it is expected that the diffusion of Cu ions in a-SiO2 nanopore without H2O is much more difficult than with H2O. This could be attributed to the strong and weak adsorption of Cu ions on the sidewall in the absence and presence of H2O, respectively, for both, a-Ta2O5 and a-SiO2. Our investigation provides a full atomic picture to understand the moisture effect on the diffusion of Cu ions in Cu/a-Ta2O5/Pt and Cu/a-SiO2/Pt resistance switches.